Tetrads and polyads in Mimosa L. (Leguminosae): an overview on pollen diversity and evolution - Liau Kang Goicochea, Stefany (2021)
Descargue el texto completo en el repositorio institucional de la Universidade de São Paulo: https://doi.org/10.11606/D.59.2022.tde-20042022-084138